2012
DOI: 10.1007/s00417-012-2159-5
|View full text |Cite
|
Sign up to set email alerts
|

Summary of prognostic factors for choroidal neovascularization due to pathological myopia treated by intravitreal bevacizumab injection

Abstract: A lower rate of development of chorioretinal atrophy, smaller pretreatment CNV size, and younger age were indentified as the most consistently significant prognostic factors affecting the efficacy of IVB in eyes of myopic CNV and were associated with improved BCVA. A worse BCVA after IVB in eyes with myopic CNV probably was associated with subfoveal CNV, lower baseline BCVA, longer duration of CNV, incomplete regression of CNV, subretinal hemorrhage, and previous PDT treatment. No apparent association were obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 30 publications
0
16
0
4
Order By: Relevance
“…Several studies have shown that the presence of chorioretinal atrophy is a factor predictive of poor visual acuity following anti-VEGF treatment [28] . Moreover, it has been well established that the long-term enlargement of the area of chorioretinal atrophy around the mCNV lesion is one of the main prognostic factors for a worse final visual acuity outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the presence of chorioretinal atrophy is a factor predictive of poor visual acuity following anti-VEGF treatment [28] . Moreover, it has been well established that the long-term enlargement of the area of chorioretinal atrophy around the mCNV lesion is one of the main prognostic factors for a worse final visual acuity outcome.…”
Section: Discussionmentioning
confidence: 99%
“…9,10,30 Deste modo, e tendo em conta os resultados não sustentados com a terapia fotodinâmica, os novos fármacos antiangiogénicos têm sido cada vez mais utilizados no tratamento de patologias que cursam com NVC, como é o caso da miopia patológica.…”
Section: Discussionunclassified
“…Assume particular interesse no tratamento da NVC na miopia, pelos resultados promissores descritos em séries de casos e alguns ensaios clínicos, 1,6,8,11,13,[34][35][36] aliados a um preço significativamente mais baixo quando comparado com o ranibizumab, permitindo deste modo que a terapêutica seja acessível a um maior número de doentes. 10 Verificámos que os agentes antiangiogénicos permitiram uma melhoria significativa e sustentada na MAVC e na EF, até aos 60 meses de tratamento. Os nossos resultados estão de acordo com outros descritos para o ranibizumab [37][38][39][40][41] e para o bevacizumab em estudos com menor tempo de seguimento.…”
Section: Discussionunclassified
See 2 more Smart Citations